2023
DOI: 10.3390/microorganisms11030671
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies to Combat Fungal Infections: Development Strategies and Progress

Abstract: The finding that some mAbs are antifungal suggests that antibody immunity may play a key role in the defense of the host against mycotic infections. The discovery of antibodies that guard against fungi is a significant advancement because it gives rise to the possibility of developing vaccinations that trigger protective antibody immunity. These vaccines might work by inducing antibody opsonins that improve the function of non-specific (such as neutrophils, macrophages, and NK cells) and specific (such as lymp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 165 publications
(127 reference statements)
0
2
0
Order By: Relevance
“…Unfortunately, there are currently no therapeutic vaccines licensed against fungal infections for human or veterinary use. A variety of studies have shown the positive effect of antibody administration against fungal infection, alone or in combination with antifungal drugs [ 108 ]. One of the most known studies is on Efungumab (Mycograb ® ), a human genetically recombinant antibody that binds to Candida ’s HSP90, protecting against several Candida species and synergizing with antifungal drugs when evaluated in vitro and in preclinical studies [ 109 ].…”
Section: Immune Response Against Fungal Infections and Approaches Vac...mentioning
confidence: 99%
“…Unfortunately, there are currently no therapeutic vaccines licensed against fungal infections for human or veterinary use. A variety of studies have shown the positive effect of antibody administration against fungal infection, alone or in combination with antifungal drugs [ 108 ]. One of the most known studies is on Efungumab (Mycograb ® ), a human genetically recombinant antibody that binds to Candida ’s HSP90, protecting against several Candida species and synergizing with antifungal drugs when evaluated in vitro and in preclinical studies [ 109 ].…”
Section: Immune Response Against Fungal Infections and Approaches Vac...mentioning
confidence: 99%
“…Elevated Th2 [10,[21][22][23] and Th17 responses [10,24] have been associated with poor outcomes, with Th1/Th2 [25][26][27] and Th1/Th17 imbalances [28] also reported to be detrimental. T regulatory cells (Tregs) are viewed as providing protection against the cytokine storm [29], whereas neutrophils promote the latter and contribute to disease severity [10]. Monocytes and macrophages play key protective roles against SARS-CoV-2 infection, but depending on their differentiation and activation state, are also important contributors to over-production of inflammatory cytokines [30,31].…”
Section: Introductionmentioning
confidence: 99%